1989
DOI: 10.1021/jm00129a031
|View full text |Cite
|
Sign up to set email alerts
|

Benzofuro[2,3-c]pyridin-6-ols: synthesis, affinity for opioid-receptor subtypes, and antinociceptive activity

Abstract: A general synthetic approach to a novel series of cis-1,2,3,4,4a,9a-hexahydrobenzofuro[2,3-c]pyridin-6-ols is described together with their receptor-binding profile on opioid-receptor subtypes (mu, kappa, delta). In addition, their in vivo antinociceptive activity was assessed. A number of the analogues synthesized showed potent affinity for opioid receptors and have potent antinociceptive activity in a mouse phenylquinone abdominal stretching model. In addition, the SAR for nitrogen substitution in the above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 3 publications
0
36
0
Order By: Relevance
“…In the C4a-alkyl, N -methyl series 2f–j , the affinity for μ receptors was optimal when C4a was ethyl, in 2g , as found by Hutchison et al, 2 and the compound with the highest affinity at δ-receptors was determined to be 2j , with a C4a-pentyl group ( K i = 33 nM, Table 1). The affinity increased with chain-length, from propyl ( 2h , K i = 479 nM) to butyl ( 2i , K i = 207 nM) to pentyl ( 2j , K i = 33 nM).…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…In the C4a-alkyl, N -methyl series 2f–j , the affinity for μ receptors was optimal when C4a was ethyl, in 2g , as found by Hutchison et al, 2 and the compound with the highest affinity at δ-receptors was determined to be 2j , with a C4a-pentyl group ( K i = 33 nM, Table 1). The affinity increased with chain-length, from propyl ( 2h , K i = 479 nM) to butyl ( 2i , K i = 207 nM) to pentyl ( 2j , K i = 33 nM).…”
Section: Resultsmentioning
confidence: 60%
“…2 Benzofuro[2,3- c ]pyridinols are partial structures of oxide-bridged phenylmorphans. Although they appear to be structurally similar to the d-series of the oxide-bridged phenylmorphans, 35 the presence of a truncated C4a group gives the benzofuropyridinols a flexibility that is lacking in the rigid oxide-bridged phenylmorphans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our work[1-3] and that of Hutchison et al[4] it has been shown that cis -1,2,3,4,4a,9ahexahydrobenzofuro[2,3- c ]pyridin-6-ols ( 1 , Fig. 1), when suitably substituted on the tertiary nitrogen and the C4a-position, have high or moderate affinity for either μ-, δ- and κ-opioid receptors, and sometimes at a combination of these receptors [4].…”
Section: Introductionmentioning
confidence: 85%
“…1), when suitably substituted on the tertiary nitrogen and the C4a-position, have high or moderate affinity for either μ-, δ- and κ-opioid receptors, and sometimes at a combination of these receptors [4]. In principle, then, substituent modifications at these positions could lead to compounds that interact with a desirable combination of trueμ~ and δ-opioid receptor affinity.…”
Section: Introductionmentioning
confidence: 99%